Integration mot alla odds? - Henrik Carlsson, Carl (2025)
In 2017 a conflict erupted among the Bosniaks in Bosnia and Herzegovina. It was related to identity and self-image, in particular the role of Bosnian Muslims during World War II. Highly sensitive but seldom discussed issues were brought to the fore. Had not Muslim forces massacred Serb villages? Did not Croat and Muslim Ustasha kill most of the Jews in Bosnia? Why, then, regard antisemitic collaborators as national role models? Reactions varied from condemnation to arguments that Muslims acted in self-defence. Even antisemitic rhetoric appeared. There was a divide between a liberal, secular opinion and religious-national views within the ruling party or the Islamic Community. Apparently, a certain continuity existed between Muslim elites during World War II and those in power since 1990. In the 1930s, Bosnian Muslims were familiar with currents in the Middle East, the ideas of the Muslim Brotherhood and the anti-Jewish message of the Mufti of Jerusalem. The organization Young Muslims, inspired by Islamist ideas from Egypt, was violently suppressed by the Communists 1945–48, but reappeared in 1990, forming the nucleus of the Party of Democratic Action, led by Alija Izetbegović. After the war, high-level contacts with the Muslim Brothers were cordial and regular. The crisis revealed tensions between the religious foundation of Bosniak identity and the building of a modern nation. Parts of society had been nurturing a discourse of martyrdom where history had to be ignored or revised. The study deals with the conflict in recent years, as well as with the ideas of Mustafa Busuladžić and the historical context in which he was active. Besides texts by Busuladžić and his contemporaries, I have relied on Bosnian sources, as well as international research.